2020
DOI: 10.1002/ncp.10487
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Associated With Commercial and Homemade Blenderized Tube Feedings: A Literature Review

Abstract: There is emerging evidence in the pediatric population that blenderized tube feeding (BTF) may improve gastrointestinal intolerance; however, not much is known about the impact of BTF on clinical outcomes in adults. This article presents a review of the literature published in the past 10 years that explored the impact of BTF on nutrition status (ie, weight status, body mass index, and upper-arm circumference) and nutrition adequacy in adults. The results indicate that BTF, compared with commercial enteral for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
(175 reference statements)
0
10
0
5
Order By: Relevance
“…Sutanto et al 31 found that the values for energy and macronutrients in all the enteral formulations that they studied showed high degrees of variation in relation to accuracy. A study by Brown et al 32 indicated that blenderized tube feedings (BTFs), compared with CEFs, may be inadequate in terms of energy, macronutrients, and some micronutrients, given the variability in the composition of BTF formulas. Jolfaie et al 33 also verified that CEF samples contained more energy, carbohydrate, and fat compared with HEP samples; however, the protein intake was less than the required amount.…”
Section: Discussionmentioning
confidence: 99%
“…Sutanto et al 31 found that the values for energy and macronutrients in all the enteral formulations that they studied showed high degrees of variation in relation to accuracy. A study by Brown et al 32 indicated that blenderized tube feedings (BTFs), compared with CEFs, may be inadequate in terms of energy, macronutrients, and some micronutrients, given the variability in the composition of BTF formulas. Jolfaie et al 33 also verified that CEF samples contained more energy, carbohydrate, and fat compared with HEP samples; however, the protein intake was less than the required amount.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review completed by Brown et al 67 in 2020 evaluated outcomes of BTF on nutrition status (weight, body mass index [BMI], and upper‐arm circumference [UAC]) and nutrition adequacy in adults. Results noted that BTF may be inadequate in calories, macronutrients, and some micronutrients because of the variability of BTF formula composition leading to decline in weight status, BMI, and UAC 67 . The studies reviewed showed a trend toward more positive clinical outcomes with commercial enteral formulas and suggested home‐blended formulas may not be appropriate for adults who are malnourished, thereby reserving home‐blenderized EN for the stable adult patient with a clinical support system and ability to prepare nutritionally adequate BTF 67 …”
Section: Review Of En Formulationsmentioning
confidence: 99%
“…66 After transition to plant-based EN fecal samples showed microbiota similar to their healthy controls. 66 A literature review completed by Brown et al 67 in 2020 evaluated outcomes of BTF on nutrition status (weight, body mass index [BMI], and upper-arm circumference [UAC]) and nutrition adequacy in adults. Results noted that BTF may be inadequate in calories, macronutrients, and some micronutrients because of the variability of BTF formula composition leading to decline in weight status, BMI, and UAC.…”
Section: Overall Recommendations With Immune-enhancing Formulasmentioning
confidence: 99%
See 1 more Smart Citation
“…Blenderized formulas are less likely to contain food allergens, may be organic and vegan, and contain naturally occurring antioxidants not found in traditional commercial EN formulas. Patients have anecdotally reported improved GI tolerance to these formulas, although there is as yet limited evidence from randomized controlled trials on the benefit of blenderized formulas in patients with a GI intolerance for standard formulas or those with specific disease states [ 36 , 37 , 38 ].…”
Section: En Formulasmentioning
confidence: 99%